EMOTIONAL EXPRESSIVNESS OF GENDER IDENTIFY WORDS IN ENGLISH AND UZBEK - Feruza Muhammadjonova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
There is distinct difference among the features of genders. As well as, emotional words related to gender not only increase the richness of the speech , but also serve to convey it directly to the listener and increase its effectiveness. Such words can be found in every country's culture and speech style.